2013
DOI: 10.1007/s10646-013-1124-3
|View full text |Cite
|
Sign up to set email alerts
|

Toxic effects of Triclosan on the detoxification system and breeding of Daphnia magna

Abstract: The toxic effects of different concentrations of Triclosan (TCS) (1-128 μg/L) on Daphnia magna (D. magna) were investigated by acute (48 h) and chronic (21-day) toxicity tests. The response of antioxidase system and Phase I metabolism process of D. magna exposed to TCS were investigated by measuring a series of biomarkers including glutathione S-transferase (GST), catalase (CAT), superoxide dismutase (SOD), malondialdehyde (MDA), 7-ethoxyresorufin O-deethylase (EROD), Erythromycin N-demethylase (ERND) and Amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(28 citation statements)
references
References 59 publications
6
22
0
Order By: Relevance
“…We observed a concentration-dependent drop in reproduction during triclosan exposures from 0.022 – 0.345 μM, but it was not statistically significant by ANOVA. Previous studies reported 0.22 μM (64 μg/L) triclosan reduced reproduction during chronic toxicity tests with D. magna (Peng et al, 2013). To our knowledge, this is the first paper to report the reproductive toxicity of DHA or LA (Suppl File 1).…”
Section: Resultsmentioning
confidence: 92%
“…We observed a concentration-dependent drop in reproduction during triclosan exposures from 0.022 – 0.345 μM, but it was not statistically significant by ANOVA. Previous studies reported 0.22 μM (64 μg/L) triclosan reduced reproduction during chronic toxicity tests with D. magna (Peng et al, 2013). To our knowledge, this is the first paper to report the reproductive toxicity of DHA or LA (Suppl File 1).…”
Section: Resultsmentioning
confidence: 92%
“…Previous studies have examined the acute toxicity of triclosan, carbamazepine and ibuprofen to D. magna and reported 48 hour LC 50 (the concentration that causes 50% mortality) values of 7 330 µg/L, mg/L, 132.6 mg/L, respectively (Han et al, 2006;Peng et al, 2013) After preliminary tests to confirm the hour sub-lethal contaminant concentrations, D. magna adults were exposed over 48 hours to either sub-lethal triclosan concentrations (0, 6.25, 12.5, 25, 50, 75 and 100 µg/L), sub-lethal carbamazepine concentrations (0, 1.75, 3.5, 5.25, 7, 10.5 and 14 mg/L) or sub-lethal ibuprofen concentrations (0, 1.75, 3.5, 5.25, 7, 10.5 and 14 mg/L). For every exposure concentration, two groups of 60 individuals each were kept in separate 2 L beakers with a density of 1 daphnid per 30 mL.…”
Section: Daphnia Exposure To Sub-lethal Concentrations Of Triclosan mentioning
confidence: 99%
“…The biocide triclosan inhibits the enoyl-acyl carrier protein reductase (ENR), which is involved in the bacterial lipid biosynthesis, so bacteria are unable to reproduce (Heath and Rock, 2000). In D. magna, triclosan enhances the activity of glutathione S-transferase (GST), and decreases the superoxide dismutase (SOD) activity, which may indicate damage in the cell membranes, confirming that triclosan causes oxidative stress (Peng et al, 2013).…”
Section: Introductionmentioning
confidence: 99%